Rebels and exiles: a biblical theology of sin and restoration - Harmon, Matthew S. (Essential studies in biblical theology, 2020)
"We all share an experience of exile-of longing for our true home. In this ESBT volume, Matthew S. Harmon explores how the theme of sin and exile is developed throughout Scripture, tracing a common pattern of human rebellion, God's judgment, and the hope of restored relationship, beginning with the first humans and concluding with the end of exile in a new creation"--